2000
DOI: 10.1002/pc.10211
|View full text |Cite
|
Sign up to set email alerts
|

Applications of fiber‐metal laminates

Abstract: Advanced composite materials and fiber‐metal laminates (FMLs) have the potential to offer significant improvements in weight savings and durability in airframe structures. FMLs are an advanced hybrid material system consisting of metal layers bonded with fiber‐reinforced polymer layers. This paper presents an overview of the history of fibre‐metal‐laminates, describes several common types and also discusses the results of impact durability experiments conducted at the Structures, Materials and Propulsion Labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…In literature [17][18][19], the major part of Fiber-Metal Laminates (FMLs), due to their advantages, is used in modern aircraft parts, such as fuselage, wings, etc. FMLPs are used as manufactured or after paint application.…”
Section: Cosmetic Characterizationmentioning
confidence: 99%
“…In literature [17][18][19], the major part of Fiber-Metal Laminates (FMLs), due to their advantages, is used in modern aircraft parts, such as fuselage, wings, etc. FMLPs are used as manufactured or after paint application.…”
Section: Cosmetic Characterizationmentioning
confidence: 99%
“…ARALL found its first application in C17 cargo doors. Some of the other major applications of fibre metal laminations in avaiation industry were found in the Ref [2]. By combining the isotropic, plastic behavior, durability characteristic, impact resistance, easy repair of metals and superior strength, stiffness, excellent fatigue, fracture characteristics of composite materials; FML was developed as a material having superior fatigue resistance, excellent impact characteristics, having low density and adequate corrosion resistance property [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight FMLs are widely used in the aerospace industry due to their remarkable fatigue and impact properties . Researchers have shown that the existence of fibers in the composite layers acted as a barrier against crack propagation, and they increase the burn rate through resistance as well as damping and insulation properties, while the metal layers provide high impact resistance and damage tolerance in the FMLs . The first generation of thermoset‐based FMLs which consist of aramid fiber prepreg sandwiched with aluminum plates, namely ARALL (Aramid‐reinforced aluminum laminate), were successfully developed in Delf University of Technology.…”
Section: Introductionmentioning
confidence: 99%